Mesenchymal Stem Cells as A New Approach for the Treatment of Multiple Sclerosis: A Literature Review : - Jafarinia, Morteza; Rostami, Amirabbas; Abbasi, Yusef; Asadian, Asma; Enani, Hossein; Jamalnia, Sheida (Galen Medical Journal, 2022)
Multiple sclerosis (MS) is a high-prevalence autoimmune and neurodegenerative disease that affects young adults. An ideal treatment for MS should have two characteristics. First, its immunosuppression and immunomodulation effects reduce the abnormal immune response, and second, it improves repair by enhancing intrinsic repair processes or even cell replacement. Most available therapies have the first characteristic. Recent studies have proposed mesenchymal stem cells (MSCs) as a new therapeutic candidate for MS. Different clinical trials and animal models of MS have shown the therapeutic effect of MSCs. In the current study, we reviewed the therapeutic effects of MSCs in the animal model and patients with MS.